2003
DOI: 10.1002/app.12614
|View full text |Cite
|
Sign up to set email alerts
|

Water transport, structure features and mechanical behavior of biodegradable PHB/PVA blends

Abstract: Stochastic programming is a typical method for addressing the uncertainties in capacity expansion planning problem. However, the corresponding deterministic equivalent model is often intractable with considerable number of uncertainty scenarios especially for stochastic integer programming (SIP) based formulations. In this article, a hybrid solution framework consisting of augmented Lagrangian optimization and scenario decomposition algorithm is proposed to solve the SIP problem. The method divides the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
(16 reference statements)
2
26
0
Order By: Relevance
“…3 Previous studies have shown that the sorption and diffusion phenomena took place exclusively in the amorphous phase of a semicrystalline polymer and not in its crystalline zones. 4,5 The crystalline portion increases the effective path length of gas diffusion, and they seem to reduce the polymer chains mobility in the amorphous phase (because chain ends are trapped in the neighboring crystalline lamellae).…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies have shown that the sorption and diffusion phenomena took place exclusively in the amorphous phase of a semicrystalline polymer and not in its crystalline zones. 4,5 The crystalline portion increases the effective path length of gas diffusion, and they seem to reduce the polymer chains mobility in the amorphous phase (because chain ends are trapped in the neighboring crystalline lamellae).…”
Section: Introductionmentioning
confidence: 99%
“…As a rule, blending has been known as a strategy of tailoring the properties of PHAs while maintaining biodegradability 67 . Blending of PHB and PHBV with other biopolymers including starch [89][90][91] , thermoplastic starch, PLA 92 , PCL 13,93,94 , and polyvinyl alcohol (PVOH) 91 are reported. In addition, there are some reports on PLA blending with different polymers e.g.…”
Section: Blendingmentioning
confidence: 99%
“…Besides, solubility and diffusivity of water in PHAs is a key factor for their degradation via enzymatic or non-enzymatic hydrolysis [120][121][122] . The water transport properties of PHB and PHBV films and their blends with other biodegradable polymers in different process conditions are reported 65,94,[115][116][117]120,121,[123][124][125] . PHAs can decrease the water sensitivity of other biopolymers 94 .…”
Section: Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The first factor was the effect of additives mixed with perylene. With respect to the diffusion of penetrant in polymer materials, free volume theory was proposed in 1960s 39 and recently, it has been generally thought that amorphous portion in polymer material is dominating diffusion pathway [40][41][42][43][44][45][46] . It was considered that with the diffusion of TEGDA or GTA, amorphous portion, i.e.…”
Section: Film Depth Dependence Of Diffusion Coefficientmentioning
confidence: 99%